(untitled) (Journal of Environmental Microbiology and Toxicology, 2014)
Effect of heavy metals was tested on Serratia marcescens strain AQ07 (accession number: KP213291) to affirm its effect on growth and biodegradation of cyanide. 1 ppm of ten different heavy metals was experimented in-vitro in buffer medium containing 200 ppm potassium cyanide. They are: silver, arsenic, cadmium, cobalt, chromium, cupper, mercury, nickel, lead and zinc. The results obtained illustrates that mercury have significant effect on the growth (optical density 0.13) and biodegradation of cyanide removing only 24.7% compared to the control which has no incorporation of heavy metal (optical density 0.74 and 92% removal respectively) while others remove above 80%. Further studies on mercury reveal that it has significant effect on the bacteria even as low as 0.1 ppm. This illustrates that mercury can significantly hinder biodegradation of cyanide by Serratia marcescens strain AQ07.